2020
DOI: 10.3390/brainsci10060337
|View full text |Cite
|
Sign up to set email alerts
|

Hand Fine Motor Skill Disability Correlates with Cognition in Patients with Moderate-to-Advanced Parkinson’s Disease

Abstract: In older individuals, hand fine motor skill disability is associated with cognitive levels. Similarly, patients with moderate-to-advanced Parkinson’s disease (PD) often have cognitive dysfunction. Here, we investigated the association between hand fine motor skill and cognitive dysfunction in patients with moderate-to-advanced PD. Moderate and advanced PD patients with and without dementia were identified from the Taiwan Data Bank of Persons with Disability. Hand fine motor capacities, namely pen holding, butt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
7
0
3
Order By: Relevance
“…In addition to these differences, the authors demonstrated the significant correlation of precision task with age of participants and the MiniMental State Examination results [31]. Also, pen-holding and knotting performance was significantly associated with dementia in patients with moderate-to-advanced PD, which allowed the researchers to establish there is a 13% higher probability of dementia for PD patients if they had any level of disability in pen holding [32].…”
Section: Tablementioning
confidence: 87%
See 1 more Smart Citation
“…In addition to these differences, the authors demonstrated the significant correlation of precision task with age of participants and the MiniMental State Examination results [31]. Also, pen-holding and knotting performance was significantly associated with dementia in patients with moderate-to-advanced PD, which allowed the researchers to establish there is a 13% higher probability of dementia for PD patients if they had any level of disability in pen holding [32].…”
Section: Tablementioning
confidence: 87%
“…Dahdal et al determined that people with PD and mild cognitive impairment exhibited a significant worse motor performance in precision (to guide a stylus through a narrow curved track without touching the sides), dexterity (to insert 25 long and short pins into holes in a platform), and velocity of arm-hand movement (time spent to precisely hit 20 subsequent points lined in a row) tasks [31]. Likewise, Tan et al found that people with PD and dementia have poorer hand function in pen-holding, buttoning, and knotting actions than do the patients without dementia [32]. independence or a need for assistance when accomplishing tasks (0 = total independence, 1 = need for supervision or mild assistance, 2 = need for moderate assistance, 3 = need for maximal assistance, 4 = need for total assistance).…”
Section: Hand Functionalitymentioning
confidence: 99%
“…І навпаки, показано, що розумова активність впливає на відновлення функції руки [4,5]. Відмічено, що когнітивний статус пов'язаний та залежний від дрібної моторики рук і у пацієнтів із хворобою Паркінсона [6].…”
Section: вступunclassified
“…Для оцінки когнітивних функцій пропонується вивчення параметрів когнітивних викликаних потенціалів (КВП) [11], що дозволяє аналізувати здатність розпізнати та запам'ятовувати стимул, а також тривало утримувати/концентрувати увагу. У генезі виникнення КВП Р300 при сенсорній стимуляції головного мозку задіяні такі структури, як скронево-тім'яна ділянка, мотор на кора, верхня скронева звивина, інсула, префронтальна та дорзолатеральна кора, гіпокамп та амігдала, тому відповідь є результатом їх сумарного функціонування [6]. Таким чином, виділяються та аналізуються ендогенні процеси в головному мозку, пов'язані з впізнанням стимулу, його обробкою та збереженням у пам'яті.…”
Section: вступunclassified
See 1 more Smart Citation